Education and heart failure: New insights from the atherosclerosis risk in communities study and mendelian randomization study. (1st February 2021) - Liao, Li-zhen; Zhuang, Xiao-dong; Zhang, Shao-zhao; Liao, Xin-xue; Li, Wei-dong
Abstract: Introduction: We aim to characterize the nature and magnitude of the prospective association between education and incident heart failure (HF) in the Atherosclerosis Risk in Communities (ARIC) Study and investigate any causal relevance to the association between them. Methods: The final sample size was 12, 315 in this study. Baseline characteristics between education levels were compared using 1-way ANOVA test, the Kruskal-Wallis test, or the χ2 test. We used the Kaplan-Meier estimate to compute the cumulative incident of HF by education levels and the difference in estimate was compared using the log-rank test. Cox hazard regression models were used to explore the association between education levels and incident HF. Two-sample Mendelian randomization (MR) based on publicly available summary-level data from genome-wide association studies (GWASs) was used to estimate the causal influence of the education and incident HF. Results: During a median follow-up of 25.1 years, 2453 cases (19.9%) of incident HF occurred. After multiple adjustments in the final model, participants in the intermediate and advanced education levels were still associated with 18% and 21% decreased rate of incident HF separately. In MR analysis, we detected a protective causal association between education and HF ( P = 0.005). Conclusions: Participants with higher education levels were associated with a decreased rate of incident HF. There was a causal association between education and HF. Highlights: Education is well known for its inverse association with cardiovascular diseases. Participants with higher education levels were associated with decreased rate of incident heart failure (HF). Mendelian randomization (MR) analyses supported a protective causal association between education and HF.